A Novel Architecture of Radix-3 Singlepath Delay Feedback (R3SDF) FFT Using MCSLA - Periyarselvam K; Saravanakumar G; Anand M (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Fast Fourier transform (FFT) is widely used in digital signal processing and telecommunications, particularly in orthogonal frequency division multiplexing systems, to overcome the problems associated with orthogonal subcarriers. A new algorithm of radix-3 FFT has been introduced in this work. The DFT of length N can be realized from three DFT sequences; each of length N/3.Radix-3 algorithm reduces the number of multiplications required for realizing DFT.A novel design of Radix-3pipelined Single path Delay Feedback (R3SDF) FFT using MCSLA has been proposed in this paper. First, the pipelined radix-3 SDF FFT method has been designed. It has less area and large power consumption and delay. In order to overcome these problems, modified carry select adder structure is used to perform the adder operation for reducing the power consumption and delay. Finally, the MCSLA is integrated into radix-3 SDF FFT processor. The hardware complexity and execution time for implementing radix-3 FFT algorithm can be reduced than other FFTs.